Jouissance, Scapegoating and the Lack of the Symbolic: What Causes the Subject's Desire and Why? - Drousioti, Kalli (Critical horizons : journal of social & critical theory, 2024)
The Lacanian theory describes the subject in terms of split and lack. It does so by illustrating the process by which the subject becomes constructed. In the present article, I critically engage with the version of Lacanian theory that Yannis Stavrakakis has promoted and with the shift that has marked the development of this version. I argue that the shift in question reveals Stavrakakis' initial misreading of Jacques Lacan and sheds light on some of the implications of the Lacanian theory of subjectivity for theorizing socio-political issues of identity operations. The misconception of important and interconnected aspects of the theorization of the subject as desiring and lacking makes room for ontologizing the incrimination of an "enemy". However, I argue, demonizing an "enemy" should not be interpreted as resulting from the fundamental desire for meaning enclosure. It is rather correlated with the jouissance that is lost in the process of the subject construction and, by implication, with the affect invested in identity (the collective identity notwithstanding). Setting the record straight allows alternative (re)conceptualizations of (collective) identity that de-naturalize the modernist assumption that the construction of a present enemy is ontologically tied with, and thus, indispensable to, (collective) identity construction.